2020
DOI: 10.1021/acsomega.0c00887
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Studies and In Vivo MAOA Inhibitory Activity of Coumarins Isolated from Angelica archangelica Extract: An Approach toward Antidepressant Activity

Abstract: The current investigation was aimed at in vivo MAOA inhibitory activity of coumarins angelicin, bergapten, and scopoletin isolated from the roots of Angelica archangelica. The isolated compounds were screened for MAOA (pdb ID 2Z5y) binding through molecular docking studies. The molecular docking results displayed that bergapten has a maximum affinity for MAOA, followed by angelicin and scopoletin. In silico prediction of physicochemical parameters indicated that maximum blood–brain barrier (BBB) permeability w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
1
7
0
2
Order By: Relevance
“…In reserpine‐induced depression of mice model, bergapten was proved to have the ability to inhibit MAOA activity. In consonance with the results of inhibiting MAOA activity in vivo, the molecular docking results displayed that bergapten has a maximum affinity for MAOA (Kaur et al, 2020). Therefore, the above studies indicated that bergapten could be used to treat some brain diseases, and the related mechanisms called for further research.…”
Section: Pharmacological Effects Of Bergaptensupporting
confidence: 63%
“…In reserpine‐induced depression of mice model, bergapten was proved to have the ability to inhibit MAOA activity. In consonance with the results of inhibiting MAOA activity in vivo, the molecular docking results displayed that bergapten has a maximum affinity for MAOA (Kaur et al, 2020). Therefore, the above studies indicated that bergapten could be used to treat some brain diseases, and the related mechanisms called for further research.…”
Section: Pharmacological Effects Of Bergaptensupporting
confidence: 63%
“…Absorption, Distribution, Metabolism, Excretion/Toxicity (ADME/T) attributes of the selected compounds were evaluated using Swiss-ADME tool ( Kaur et al, 2020 ). These played an important role in analyzing drug filtration and predict other pharmacodynamic parameters of complex consequentially aiding towards determination of potent TMPRSS2 inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…The structures of various chemical constituents of essential oils of A. archangelica are given in Figure 1. The variability in the percentage content of different essential oil constituents has been observed with variations in growing altitudes, analysis techniques, genetic diversity, harvesting conditions, and geographic diversity (Kaur et al, 2020a). The biological activities attributed to essential oils include antioxidant activity, antiinflammatory activity, antimicrobial, antiviral, and immunotoxin (Sowndhararajan, Deepa, Kim, Park, & Kim, 2017; Voon, Bhat, & Rusul, 2012).…”
Section: Chemical Constituents Of a Archangelicamentioning
confidence: 99%
“…The composition of coumarins varies according to the type of raw material, method of extraction, geographic diversity, extraction conditions, and growing conditions (Forycka & Buchwald, 2019). Coumarins are documented for a variety of pharmacological activities in preclinical investigations, such as analgesic (Kaur et al, 2020a), antiinflammatory activity (Grover & Jachak, 2015), anti‐anxiety activity (Budzynska et al, 2012; Kumar et al, 2013), antioxidative activity (Cao, Zhang, Wang, & He, 2014; Kaur, Garg, et al, 2020a; Kaur, Singh, et al, 2020b), and antiseizure activity (Luszczki et al, 2007; Luszczki, Andres‐Mach, Gleńsk, & Skalicka‐Woźniak, 2010).…”
Section: Coumarinsmentioning
confidence: 99%